Konstruksi Wanita Salihah Dalam Tafsir Visual: Analisis Kritis Terhadap Meme QS. Al-Ahzab: 33 - Kaisar Ahmad Al Jauhari; Shera Diva Zahiyah; Dafa Aqila Musyaffa'; Nilna Muna Aisyi; Lina Fatikasari (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2023)
On social media, QS. Al-Ahzab: 33 meme is spreading massively. which is used as a medium to construct women's piety. This meme has big implications for understanding how pious women are. However, studies on related memes appear to be disproportionate. This study focuses on the main issue, namely how QS. Al-Ahzab: 33 visualized, used as a tool to construct women's piety, and its relevance in the context of life and religion in Indonesia? In explaining these three issues, this study uses a content analysis approach. The results of this study show three things. First, pious women are visualized by the existence of a house that tends to be beautiful, comfortable and luxurious. Second, the construction of pious women becomes real by presenting a visualization that seems to emphasize that pious women are synonymous with home. This is also reinforced by the title in the picture, namely